2020
DOI: 10.1155/2020/3038564
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Produced Monoclonal Antibody as Immunotherapy for Cancer

Abstract: Plant-based products have expanded to include cancer immunotherapy, which has made great strides over recent years. Plants are considered inexpensive and facile production platforms for recombinant monoclonal antibody (mAb) due to the latest advancements and diversification of transgenic techniques. Current human biologics, including those based on mAbs produced by fermentation technologies using primarily mammalian cell cultures, have been replaced by plant-produced mAbs, which are cost effective, more scalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant stable transformation allows the development of genetically modified (GM)/transgenic plants with well-defined master and working seed banks to be used for consecutive batches, leading to large-scale production [ 31 , 32 ]. Furthermore, cross-fertilization between transgenic plants producing two different recombinant proteins can generate siblings that express multiple recombinant genes, an approach useful for monoclonal antibodies purification [ 33 ].…”
Section: Transformation Technologies and Crispr-cas Genome Editing Methodsmentioning
confidence: 99%
“…The plant system offers important advantages, such as high production capacity, low cost in the large-scale cultivation process, in addition to avoiding ethical problems associated with animals [98]. Another important advantage of using this system is found in post-translational protein modifications, which occur in plant cells in a similar way to animal cells, as well as in the correct assembly of complex molecules, such as antibodies, are aided by chaperones that mediate folding and the formation of disulfide bonds, while the addition of N-glycans is carried out by specific cellular glycosyltransferases.…”
Section: Plant-based Antibody Production Systemsmentioning
confidence: 99%
“…It is possible to put the product on the market quickly, which ends up decreasing the cost of production. Plants also reduce screening costs for bacterial toxins, viruses, and prions because they are less likely to introduce animal pathogens than mammalian cells or animals [98].…”
Section: Plant-based Antibody Production Systemsmentioning
confidence: 99%